E-Skin Bimodal Sensors for Robotics and Prosthesis Using PDMS Molds Engraved by Laser † - dos Santos, Andreia (Sensors (Basel), 2019)
Electronic skin (e-skin) is pursued as a key component in robotics and prosthesis to confer them sensing properties that mimic human skin. For pressure monitoring, a great emphasis on piezoresistive sensors was registered due to the simplicity of sensor design and readout mechanism. For higher sensitivity, films composing these sensors may be micro-structured, usually by expensive photolithography techniques or low-cost and low-customizable molds. Sensors commonly present different sensitivities in different pressure ranges, which should be avoided in robotics and prosthesis applications. The combination of pressure sensing and temperature is also relevant for the field and has room for improvement. This work proposes an alternative approach for film micro-structuration based on the production of highly customizable and low-cost molds through laser engraving. These bimodal e-skin piezoresistive and temperature sensors could achieve a stable sensitivity of −6.4 × 10(−3) kPa(−1) from 1.6 kPa to 100 kPa, with a very robust and reproducible performance over 27,500 cycles of objects grasping and releasing and an exceptionally high temperature coefficient of resistance (TCR) of 8.3%/°C. These results point toward the versatility and high benefit/cost ratio of the laser engraving technique to produce sensors with a suitable performance for robotics and functional prosthesis.